2019
DOI: 10.4467/20843879pr.19.011.10894
|View full text |Cite
|
Sign up to set email alerts
|

Postawy wobec globalizacji a satysfakcja z życia. Mediacyjna rola procesów tożsamościowych

Abstract: Attitudes toward Globalization and Life Satisfaction The Mediating Role of Identity Formation The aim of the research was to describe the relationship between attitudes toward globalization and life satisfaction and identity processes in the group of young adults. The sample included of 403 people at the age of 19–35 (M = 22.84, SD = 2.81), 219 women (54.3%) and 184 men. The relations were measured with the use of three questionnaires: Questionnaire of Attitudes Toward Globalization (Senejko, Łoś, 2016), Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Results from pre-pandemic studies have shown no correlation between attitudes towards globalization and life satisfaction (Jasiński et al, 2019). The results of research conducted during the first wave of the pandemic in Poland indicate that the context of the pandemic, understood as a manifestation of globalization, clearly strengthens the correlation between fearful attitude towards globalization and life satisfaction (Jasiński, Bąkowska, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Results from pre-pandemic studies have shown no correlation between attitudes towards globalization and life satisfaction (Jasiński et al, 2019). The results of research conducted during the first wave of the pandemic in Poland indicate that the context of the pandemic, understood as a manifestation of globalization, clearly strengthens the correlation between fearful attitude towards globalization and life satisfaction (Jasiński, Bąkowska, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Globalization may be one of the most important features of the modern world, towards which the individual needs to assume specific attitudes (Reese et al 2019). Earlier research shows that there is no direct correlation between attitudes towards globalization and life satisfaction (Jasiński et al 2019), while most recent studies indicate that the COVID-19 pandemic is inversely related to life satisfaction (Yang and Ma 2020). It is possible that the new circumstances resulting from the global threat posed by an infectious disease intensified the correlation between the evaluation of globalization and life satisfaction.…”
Section: Attitudes Towards Globalization Life Satisfaction and Covid-19 Pandemicmentioning
confidence: 98%